Willingness To Use E-Collection System In State-Owned Tertiary Institutions: Moderating Effect Of E-Collection Training - Haruna, Sulaiman (2019)
The absence of effective and adequate means of revenue generation in Nigeria has necessitated the federal government to introduce and adopt Treasury Single Account (TSA) through the full implementation of e-payment and electronic revenue collection system (e-collection system). This has also obliged the state governments across the country to adopt the TSA system. Therefore, this current study examines the accounting staff willingness in state-owned tertiary institutions to use e-collection system. Specifically, e-collection training was employed as moderating variable to study its effect on willingness to use the new system towards technology acceptance model (TAM). In achieving the above objective, purposive sampling technique was used, and survey method was adopted by distribution a set of 110 questionnaires to users of e-collection system in nine state-owned tertiary institutions in Nigeria. Thus, a total of 102 questionnaires were useable and applied for the analysis. The statistical result from the PLS-SEM analysis demonstrated that perceived usefulness, computer self-efficacy, and attitude were all significantly influences the willingness to use e-collection system. Moreover, e-collection training moderates the relationship between attitude and willingness to use. It is recommended that the government need to provide adequate training opportunities to encourage the use of technological devices among the accounting staff, most importantly the e-collection system training.